The liberal spirit and the decline of the equalization of Womanin Las máscaras del héroe (XXI Century. Spanish Literature and Culture, 2007)
Las máscaras del héroe describes Spanish society from the months previous tothe advent of the Second Republic up until the outburst of the Civil War. A countrydivided and broken, both physically and spiritually, that brings down many wills,especially those of women. The main narrator, whose only goal is to pursue his ownbenefit, portrays a male chauvinist society which despises women in general. Aftercareful analysis, this vision proves to be bias and Colombine –a character as well as ahistoric figure- arises as a symbol of women fighting either for their rights or just fortheir own survival. The novel vindicates the voices of those who were silenced ingeneral and, specifically, of women, since many of them suffered oppression,forgetfulness and silence. Women are depicted as a reflection of the spirit of theSecond Republic.
Keywords: Second Republic, Civil War, feminism, male chauvinism, the other, degradation.